Discourse analysis as a research strategy in the field of Administration: An overview - Cabral, Augusto Cézar de Aquino (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This paper develops a reflection on Discourse Analysis (DA), which has had an increasingly meaningful role in the field of organizational studies, especially in administration. It begins with the presentation of the DA main streams, a methodological division which delimits distinct orientations both in the theoretical and practical fields. It takes Saussure’s contributions as the starting point of the theoretical foundation. After that, the theories of speech acts, or pragmatics, as well as the theories of enunciation and the concept of destination are briefly explored, as a way to establish a background to guide the reader and allow him/ her to understand the urge to submit the discourse of administration to the indiscreet DA lenses.